Diagnosis of bipolar and major depressive disorders: The appropriateness of MINI compared to the clinical interview in a sample of patients with mood disorders in tertiary mental health care - Rodrigues, Graziela Smaniotto; Pellini, Giorgia Lionço; Rocha, Rafael; Lima, Ana Flávia; Pio de Almeida Fleck, Marcelo; Panzenhagen, Alana Castro; Shansis, Flávio Milman; Capp, Edison (Journal of psychiatric research, 2024)
The Mini International Neuropsychiatric Interview (MINI) is one of the most used instruments for the assessment of Mental Disorders, playing an essential role in psychiatric research and in clinical and hospital practice. Despite this, the accuracy of the MINI, when used by a psychiatrist, is poorly studied, particularly in relation to Bipolar Disorder (BD). The early diagnosis of BD and Major Depressive Disorder (MDD) is extremely important, as it provides an opportunity for intervention that can reduce the impact on the patient's daily life and functionality. As such, this study assesses the suitability of MINI for diagnosing BD or MDD in a sample of patients with mood disorders. Agreement between the MINI and the clinical interview was assessed in a sample of 347 outpatients by calculating Cohen's kappa, sensitivity, specificity, positive predictive value, negative predictive value, and the area under the curve (AUC). The sample consisted of 347 patients with mood disorders. 279 were women (80.40%), 105 (30.3%) were diagnosed with MDD and 242 (69.7%) with BD from the assessment performed in the clinical interview. In the MINI assessment, 97 individuals (28%) were classified with a diagnosis of MDD and 250 (72%) with BD. We found a sensitivity of 87.2% and specificity of 62.8% for the MINI in the diagnosis of BD and a Cohen's kappa between the MINI and the clinical interview of 0.51. The AUC was 0.75. MINI has greater sensitivity (87.2%) for the diagnosis of BD and greater specificity (87.2%) for the diagnosis of MDD. In addition, the moderate Cohen kappa (0.51) and AUC (0.75) values between the MINI and the clinical interview are acceptable when considering most available psychiatric diagnostic tools.